Comparing external and internal validation methods in correcting outcome misclassification bias in logistic regression: A simulation study and application to the case of postsurgical venous thromboembolism following total hip and knee arthroplasty. Issue 2 (4th December 2018) - Ni, Jiayi; Dasgupta, Kaberi; Kahn, Suzan R.; Talbot, Denis; Lefebvre, Geneviève; Lix, Lisa M.; Berry, Greg; Burman, Mark; Dimentberg, Ronald; Laflamme, Yves; Cirkovic, Alain; Rahme, Elham
Abstract: Purpose: We assessed the validity of postsurgery venous thromboembolism (VTE) diagnoses identified from administrative databases and compared Bayesian and multiple imputation (MI) approaches in correcting for outcome misclassification in logistic regression models. Methods: Sensitivity and specificity of postsurgery VTE among patients undergoing total hip or knee replacement (THR/TKR) were assessed against chart review in six Montreal hospitals in 2009 to 2010. Administrative data on all THR/TKR Quebec patients in 2009 to 2010 were obtained. The performance of Bayesian external, Bayesian internal, and MI approaches to correct the odds ratio (OR) of postsurgery VTE in tertiary versus community hospitals was assessed using simulations. Bayesian external approach used prior information from external sources, while Bayesian internal and MI approaches used chart review. Results: In total, 17 319 patients were included, 2136 in participating hospitals, among whom 75 had VTE in administrative data versus 81 in chart review. VTE sensitivity was 0.59 (95% confidence interval, 0.48‐0.69) and specificity was 0.99 (0.98‐0.99), overall. The adjusted OR of VTE in tertiary versus community hospitals was 1.35 (1.12‐1.64) using administrative data, 1.45 (0.97‐2.19) when MI was used for misclassification correction, and 1.53 (0.83‐2.87) and 1.57 (0.39‐5.24) when Bayesian internal and external approaches were used, respectively. In simulations, all three approaches reduced the OR bias and had appropriate coverage for both nondifferential and differential misclassification. Conclusion: VTE identified from administrative data had low sensitivity and high specificity. The Bayesian external approach was useful to reduce outcome misclassification bias in logistic regression; however, it required accurate specification of the misclassification properties and should be used with caution.